Los héroes chilenos decimonónicos y su inclusión museográfica - Lucrecia Enríquez (Mélanges de la Casa de Velázquez)
This article analyses the complex process of heroification of 19th-century Chilean heroes through a proposal to create a Portrait Gallery for them, to be located in the National Museum. The idea, which by the middle of the 19th century had already found firm favour with the governing classes, took different forms, such as biographic galleries or historic and art exhibitions. When it was finally decided on a portrait gallery for eminent men at the museum, the proposal foundered on the fact that the hosting site was defined as a natural history museum.